Transdisciplinary approach to public health research - Dokmanović, Mirjana (Glasnik Advokatske komore Vojvodine, 2020)
Transdisciplinary approach to research enables the creation of new knowledge and solving complex problems and challenges of today in ways that are not hampered by narrow specialised disciplines. The work implies the potentials and importance of transdisciplinarity for the advancement of  the public health research for policies and practices in the Republic of Serbia.
Keywords: interdisciplinarity, public health, public health research, transdisciplinarity, multidisciplinarity, Republic of Serbia